Formulating strategic planning in university academic departments - Kola, M. (South African Journal of Higher Education, 2024)
The process of strategic planning permits universities to determine their respective vision and mission. Once these have been established, it is imperative to evaluate the kind of resources at a university’s disposal, and to conduct environmental analysis. Failure to plan could drive institutions into unchartered waters, which could be detrimental to their sustainability. Universities have embraced the idea of strategic management from business in order to gain a competitive advantage, and provide value to stakeholders. The purpose of this study was to investigate the way in which academic Heads of Departments (HoDs) engage in strategic planning. A qualitative research approach was employed to understand the role that these HoDs play while formulating a strategy in their respective departments. A case study research method was chosen to identify the participants, and data were collected through semi-structured, face-to-face interviews, as well as through document analysis. To ensure the credibility and dependability of the study, the same questions were posed to all of the participants. A thematic analysis technique was used to analyse the data. The results revealed that the university at which the research was conducted promoted a direct, or top-down approach in formulating their strategy. As such, the academic HoDs conformed to the university’s strategy. Future research should focus on the effectiveness of a strategy that incorporates a bottom-up, as well as a top-down approach.